The book of Urushi Japanese lacquerware from a master = Urushi no hanashi - Matsuda, Gonroku 1896-1986 (Japan library, 2019)
"Urushi, Japanese lacquerware, is perhaps the oldest and most sublime of all the Japanese arts and crafts. Its history goes back more than 7,000 years, and it is still vibrantly alive today. It is practiced by craftsmen working in time-honored techniques and by modern artists forging the future. Valued for its utilitarian durability, urushi developed into an incomparable art, adorning a multitude of objects from luxurious palaces to lavish murals and exquisitely crafted fountain pens. The present book, written more than fifty years ago by the Living National Treasure Matsuda Gonroku, has long been a must-read for collectors, researchers, and laypeople. It is the "bible" of urushi, covering every conceivable aspect of the subject. It includes some fifty full-color illustrations of masterpieces honored by history and masterworks by Matsuda himself"